2023
DOI: 10.1093/nar/gkad071
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of factors involved in the silencing of germline genes in mouse embryonic stem cells

Abstract: In mammals, many germline genes are epigenetically repressed to prevent their illegitimate expression in somatic cells. To advance our understanding of the mechanisms restricting the expression of germline genes, we analyzed their chromatin signature and performed a CRISPR-Cas9 knock-out screen for genes involved in germline gene repression using a Dazl-GFP reporter system in mouse embryonic stem cells (mESCs). We show that the repression of germline genes mainly depends on the polycomb complex PRC1.6 and DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…We observe in mouse development and hESC systems that ERH is functionally required in multiple developmental contexts to repress meiotic and gametogenic genes, as it is in S. pombe 14 , although the gene members targeted by ERH in this pathway has evolved and expanded in mammals. Our findings on meiotic gene repression are supported by the recent identification of ERH in a screen for proteins silencing germline genes in mESCs 64 . Other aspects of Erh1 function in S. pombe, such as the targeting of RNAs for degradation by the RNA exosome 14 , appear to be conserved as we observed upregulation of developmental genes typically downregulated by RNA exosome degradation 25 .…”
Section: Discussionsupporting
confidence: 77%
“…We observe in mouse development and hESC systems that ERH is functionally required in multiple developmental contexts to repress meiotic and gametogenic genes, as it is in S. pombe 14 , although the gene members targeted by ERH in this pathway has evolved and expanded in mammals. Our findings on meiotic gene repression are supported by the recent identification of ERH in a screen for proteins silencing germline genes in mESCs 64 . Other aspects of Erh1 function in S. pombe, such as the targeting of RNAs for degradation by the RNA exosome 14 , appear to be conserved as we observed upregulation of developmental genes typically downregulated by RNA exosome degradation 25 .…”
Section: Discussionsupporting
confidence: 77%
“…S14d) 66 . Most intriguingly, ncPRC1.6 is required for H3K27me3-to-5mC switching at a number of germline-specific gene promoters, although in these cases, the switch leads to maintained silencing 89,92,93 . It will be worthwhile to pursue a potential link between ncPRC1.6 and SWRs, and the possibility that ncPRC1.6 could facilitate gene activation via the same epigenetic switch mechanism that occurs at germline genes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both in vivo and in the in vitro nESC-to-EpiLC differentiation model, de novo DNA methylation depends on this initial ncPRC1.6 and SETDB1 occupancy, whereas PRC2 is dispensible ( Fig. 4 C ; Mochizuki et al, 2021 ; Al Adhami et al, 2023 ; Dahlet et al, 2021 ). Despite previous reports suggesting DNMT3B being responsible for de novo DNA methylation at germline genes and that the ncPRC1.6 component E2F6 being responsible for its recruitment ( Velasco et al, 2010 ; Dahlet et al, 2021 ), another study demonstrated redundant roles for DNMT3A and DNMT3B ( Auclair et al, 2014 ).…”
Section: Crosstalk With Dna Methylation and H3k9 Methylationmentioning
confidence: 98%